Monophyly of the Agoniatinae (Characiformes: Characidae) - Dagosta, Fernando C.p.; Datovo, Aléssio (Zootaxa, 2013)
The Characidae is the most diverse family of Neotropical fishes, currently encompassing more than one thousand valid spe-cies. Some subgroups within this family still lack phylogenetic definitions, being diagnosed on the basis of combination of characters, a common procedure in pre-cladistic studies. Agoniatinae, currently composed by two valid species, Agoniates anchovia and A. halecinus, is one of them. In the present study the Agoniatinae is redefined using a phylogenetically oriented comparative survey that included the two Agoniates species plus 114 species representing all the major clades of the Charac-idae and their closest relatives. Six derived morphological characters are identified as synapomorphies for the Agoniatinae: deep notch on the posterior region of the maxilla joining the ventral margin of the infraorbital 2; dentigerous portion of pre-maxilla shorter than the ascending process of this bone; dentary canine preceded by tricuspid teeth; ventral margin of the urohyal markedly convex; base of the uppermost ray of the ventral lobe of the caudal fin much expanded, being as deep as the distal margin of hypural 2; and levator arcus palatini muscle with a posterodorsal bundle of fibers attaching to the dorsal face of the sphenotic spine.